Will passive acoustic monitoring make result‐based payments more attractive? A cost comparison with human observation for farmland bird monitoring - Nonka Markova‐Nenova; Jan O. Engler; Anna F. Cord; Frank Wätzold (Conservation Science and Practice, 2023)
Abstract Result‐based payments (RBPs) reward land users for conservation outcomes and are a promising alternative to standard payments, which are targeted at specific land use measures. A major barrier to the implementation of RBPs, particularly for the conservation of mobile species, is the substantial monitoring cost. Passive acoustic monitoring may offer promising opportunities for low‐cost monitoring as an alternative to human observation. We develop a costing framework for comparing human observation and passive acoustic monitoring and apply it to a hypothetical RBP scheme for farmland bird conservation. We consider three different monitoring scenarios: daytime monitoring for the whinchat and the ortolan bunting, nighttime monitoring for the gray partridge and the common quail, and day‐and‐night monitoring for all four species. We also examine the effect of changes in relevant parameters (such as participating area, travel distance and required monitoring time) on the cost comparison. Our results show that passive acoustic monitoring is still more expensive than human observation for daytime monitoring. In contrast, passive acoustic monitoring has a cost advantage for nighttime as well as day‐and‐nighttime monitoring in all considered scenarios.